Effect of lower uterine segment sweeping on progress of labor in Nullipara - Boonsri Chanrachakul (2018)
Previous studies have shown that sweeping between the membranes and lower uterine segment was an effective procedure for reducing prolonged pregnancy. However, there has been no study to show the effect of lower uterine segment sweeping to the progress of the active phase of labor. This study was to determine the effect of lower uterine segment sweeping on the progress of the active phase of labor in nullipara. A total of four hundred nulliparous term pregnant women with spontaneous labor were randomized to one of two groups; the control group had routine vaginal examination while the study group had lower uterine segment sweeping at the time of each examination. Oxytocin infusion was given if there was dysfunctional labor. Progression of labor and the need for oxytocin augmentation were reviewed. Data were analyzed by chi square and Student t-test. Oxytocin was used in 67 per cent of the sweeping group and 62 per cent of the control group (p=0.3). The duration of the first stage (0.46), the second stage (0.38), and the third stage (0.28) of labor were not significantly different between the two groups. In conclusion, lower uterine segment sweeping did not reduce the need for oxytocin augmentation or lessen the duration of labor in nullipara.